Light Source Intensity Measurement using Averaging Spectroscopy Method for Optimum Usage - Nurulain Nadhirah, Shaipizaman; Nurzuraini, Omar Sharif; Sutrisno, Muhammad Siddiq Fadhil; Mohd Rashidi, Salim; Hadi, Manap (Penerbit Akademia Baru, 2023)
There are many types of light source specifically bulbs in the market with different working principles. Each of them provides different intensity at different wavelength. In order to check energy efficiency, it is not appropriate to measure intensity at certain specific wavelength for the same power rating bulb. Therefore, this paper reported the averaging spectroscopy method for intensity measurement between 400-700 nm before comparison is carried out. It is observed that the light emitting diode (LED) bulb shows to be the most efficient light bulbs with the highest average light intensity compared to incandescent and fluorescent bulbs. Light stability test is also carried out and reported in this paper.